Peranan Gaya Hidup dan Pola Makan yang Sehat Serta Tingkat Kecukupan Gizi - Cucu Rahayu; Rizky Kusuma Wardani; Yetti Wira Citerawati; Aldo Hermaya Aditia Nurkarsa (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract This study conducted a review of the interaction between dietary patterns, food nutrition, and lifestyle in relation to the assessment of health status. Dietary patterns have the advantage of considering any correlations that may exist between foods or food groups, but also between nutrients. The purpose of this research is to carry out an alternative and complementary approach in analyzing the relationship between nutrition and a healthy lifestyle. To determine dietary patterns, an index/score can be used to assess the suitability of a diet with nutritional guidelines or a predetermined pattern (a priori approach). The method used is a qualitative approach based on exploratory data (a posteriori): cluster analysis and factor analysis. Dietary patterns can vary according to gender, socio-economic status, ethnicity, culture and other factors, but more than that, the relationship between these three things can vary depending on the different relationships between these factors. Diet patterns influence health synergistically or even together with other lifestyle factors, and therefore we can refer to lifestyle patterns.